THE POTENTIAL IMPACT OF USING CHATGPT AS A SUPPORTING TOOL FOR DIRECT METHOD ON IMPROVING EFL STUDENTS’ SPEAKING SKILLS: TEACHERS’ PERSPECTIVES - Syafira, Syafira; Fithriani, Rahmah (Universitas PGRI Sumatera Barat, 2025)
Artificial intelligence (AI) is growing and starting to be applied in various aspects of English language learning, including speaking skills. In the application of the Direct Method, which emphasizes communication without translation, ChatGPT has the potential to be a support tool that can improve EFL learners' speaking skills. This study analyzes teachers' perceptions of using ChatGPT to improve EFL learners' speaking skills. Using a qualitative case study approach, the study involved 10 English teachers. Data were collected using a Likert scale questionnaire and in-depth interviews, then analyzed using thematic analysis. The results showed that most teachers had positive opinions toward integrating ChatGPT in supporting the direct method to improve students' speaking skills. However, concerns were raised regarding teacher preparation, pedagogical effectiveness, and limited feedback. This study confirms that the success of AI integration depends on teachers' willingness to optimize its use. With the right strategies, ChatGPT can be an innovative tool that complements traditional teaching methods and improves students' conversational skills.